Hyperbolic Type Traveling Wave Solution of Vakhnenko-Parkes Equation - Durur, Hülya; Yokuş, Asıf (My University, 2020)
In this article, structure of (1/???)-expansion method is applied. Another name of the reduced Ostrovsky equation, Vakhnenko-Parkes (V-P) equation is taken into consideration and exact solutions have been constructed of the (V-P) equation using (1/???)-expansion method. This method is an easier and efficient method for finding analytic solutions of nPDEs. The method appears to be easier and faster for symbolic computation.
Keywords: Matematik; Fizik; Matematik